Inclisiran for the treatment of dyslipidemia. (4th March 2018) - Nishikido, Toshiyuki; Ray, Kausik K.
ABSTRACT: Introduction : Dyslipidemia is one of the most important risk factors for cardiovascular disease. Insufficient reduction in LDL-C from existing therapies in patients at high risk of atherogenic cardiovascular disease is an unmet clinical need. Circulating PCSK9 causes hypercholesterolemia by reducing LDL receptors in hepatocytes. Areas covered : PCSK9 inhibition has emerged as a promising new therapeutic strategy to reduce LDL-C. Inclisiran, a novel, synthetic, siRNA molecule, inhibits PCSK9 synthesis in hepatocytes. Inclisiran targets intracellular PCSK9 synthesis specifically, resulting in a dose-dependent, long-term, significant reduction in LDL-C. Inclisiran has been well tolerated and safe, without severe adverse events so far. This review discusses current PCSK9 inhibitors and the results of phase I and II clinical trials of inclisiran. Expert opinion : Plasma PCSK9 enhances the degradation of LDL receptor, resulting in accumulation of LDL-C in the circulation. Current approaches with monoclonal antibodies sequester circulating PCSK9 but require frequent injections. Inclisiran inhibits translation of PCSK9 mRNA and thus switches off PCSK9 production and provides advantages over monoclonal antibodies with an infrequent dosing interval of twice a year to reduce LDL-C by over 50%. Ongoing studies will establish the long-term safety of inclisiran in patients with high cardiovascular risk and an elevated LDL-C.